Catalytically Active Coatings on the Basis of Titanium Dioxide for Ozone Destruction. Issue 1806 (2015) - Karabanov, Sergey M.; Karabanov, Andrey S.; Suvorov, Dmitriy V.; Gololobov, Gennadiy P.; Slivkin, Evgeniy V.; Klyagina, Mariya A.; Tarabrin, Dmitriy Y.
ABSTRACT: Creation of high efficiency and safe air purification systems is the important task caused by their wide use in living quarters, medical institutions, industrial areas. The most effective cleaning systems are the ozone based ones which is formed as the result of the corona or barrier discharge. The main disadvantage of these purification systems is high concentration of ozone in discharge air. The paper concentrates on the study of catalytically active coatings on the basis of titanium dioxide for effective destruction of ozone inside air purification systems. It is shown that use of catalytically active coatings of collecting electrodes on the basis of titanium dioxide and manganese oxide allows to decrease significantly (20-50%) the ozone concentration at the filter exit. As the results of the researches the following requirements have been determined: -